Titus Burckhardt ve Mimaride Dini Sembolizm - (:unkn) unknown (My University, 2017)
Titus Burckhardt, Gelenekselci Ekole mensup en önemli filozoflardan biridir.Araştırmalarını Hikmet ve Geleneğin metafizik boyutları ve onlarınsanat ve mimarideki tezahürleri üzerinde yapan Burckhardt, düşünceleriniİslam sanatı ve mimarisindeki çalışmalarıyla ortaya koymuştur. MakaledeBurckhardt’ın Gelenekselci sanat bakış açısına göre mimari yapılara dairgörüşleri ele alınmaktadır. Burckhardt’a göre, İslam mimarisinin enönemli özelliği, ‘birlik’ yani ‘tevhid’ sembolizmi dayalı bir yapıya sahip olmasıdır.Kabe, İslam’ın ilk mimari yapısı olması hem de sembolizmi bakımındanmerkezi bir öneme sahiptir. Burckhardt, İslam dini mimarisindeözellikle ikonalara yer verilmemesini Tanrı ile insan arasında hiçbir varlığınyer alamayacağını ifade eden ‘anikonizm’ ya da ‘ikonasızcılık’ olaraktanımlamaktadır.

Titus Burckhardt, was one of the most famous Traditionalist philosopher in the last century. He devoted his life to the study and exposition of the different aspects of Wisdom and Tradition. Burckhardt was one of the most remarkable exponents of universal truth, in the realm of metaphysics as well as in the realm of cosmology and of traditional art. This article aims to explain some aspects of his approach to the architecture in general and the Islamic architecture especially. The ‘unity’ is the principal dimension of the Islamic architecture. According to Burckhardt, the Kaʿba is the very primordial architecture on the earth that has an cosmologic symbolism. It has literally central importance for its architecture. Every Muslim faces the Kaʿba to recite the canonical prayers, and every mosque is accordingly orientated in this direction. For Burckhardt, the non using of image or as he says the ‘aniconism’ is also one of the most exeptional part of Islamic art and architecture. According to him, the aniconism preserves the primordial dignity of man, whose form, ‘made in the image of God’; on the other hand, nothing that could possibly be an idol, may interpose itself between man and the invisible presence of God.
Titus Burckhardt and Religious Symbolism in Architecture
Keywords: Sanat; Kültürel Çalışmalar; Din Bilimi